Logic, Rationality, and Interaction 5th International Workshop, LORI 2015, Taipei, Taiwan, October 28-30, 2015. Proceedings - van der Hoek, Wiebe; Holliday, Wesley H.; Wang, Wen-fang (Theoretical Computer Science and General Issues, 2015)
FoLLI-LNCS is the publication platform for the Association of Logic, Language and Information (FoLLI, www.folli.org). The Association was founded in 1991 to advance research and education on the interface between logic, linguistics, computer science, and cognitive science. The FoLLI Publications on Logic, Language and Information aim to disseminate results of cutting-edge research and tutorial materials in these interdisciplinary areas.    This LNCS volume  is part of FoLLi book serie and contains the papers presented at the 5th International Workshop on Logic, Rationality and Interaction/ (LORI-V), held in October 2015 in Taipei, Taiwan.  The topics covered in this program well represent the span and depth that has by now become a trademark of the LORI workshop series, where logic interfaces with disciplines as diverse as game theory and decision theory, philosophy and epistemology, linguistics, computer science and artificial intelligence.